Handbags Heaven Sdn Bhd / Afifah Batrisyia Aziz - Aziz, Afifah Batrisyia (2020)
Handbags Heaven Sdn Bhd is introducing a new product to the customers which is the fingerprints-secured bags. Our company’s aim is to give our customer a full satisfaction of having a luxury bag, with a sense of personalized and exclusive design, as well as providing them extra security to their personal belongings. This new product is produced by our company after further observation of the new trend of living style of the society, and their surroundings. Often, we are able to see people going around freely, be it for leisure, work or travelling. However, as the world revolves, crime cases have increase, annually, in a very worrying state. People may have at least heard, experienced, or saw crimes such as kidnapping, theft, pickpockets, and robbery, at least once in their life. These crimes happen almost every day, and mostly targeting the vulnerable group, such as women and kids. However, men are also not excluded from being the target for these issue.